2023
DOI: 10.3390/aerospace10020113
|View full text |Cite
|
Sign up to set email alerts
|

On the Study of Thermal-Propulsive Systems for Regional Aircraft

Abstract: Life without mobility is inconceivable. To enable this connectivity, one must find a way to progress towards a more sustainable transportation. In the aviation industry, a comprehensive understanding of greening technologies such as electrification of the propulsion system for commercial aircraft is required. A hybrid-electric propulsion concept applied to a regional aircraft is studied in the context of the FutPrInt50 project. To this end, the hybrid-electric propulsive system components are modeled, validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…An initial estimation showed a critical heat load value of 237 kW during take-off (TO). However, in a previous study by the authors [27], this value was found to be lower than 200 kW for the ATR42-600 with a parallel hybrid-electric propulsion system and the characteristics displayed in Table 2. This latter aircraft is slightly different, namely its propulsive system does not have the wingtip propeller-driven electric motors, albeit it includes two additional electric motors.…”
Section: Reference Aircraft and Missionmentioning
confidence: 72%
See 1 more Smart Citation
“…An initial estimation showed a critical heat load value of 237 kW during take-off (TO). However, in a previous study by the authors [27], this value was found to be lower than 200 kW for the ATR42-600 with a parallel hybrid-electric propulsion system and the characteristics displayed in Table 2. This latter aircraft is slightly different, namely its propulsive system does not have the wingtip propeller-driven electric motors, albeit it includes two additional electric motors.…”
Section: Reference Aircraft and Missionmentioning
confidence: 72%
“…Wingtip propellers driven by electric motors are also part of the powerplant. In this work, the main characteristics of the considered reference aircraft were the ones initially studied in the project, which are listed in Table 2 alongside those of the ATR42-600 used in [27]. This latter aircraft was chosen as the category benchmark in the project [28].…”
Section: Reference Aircraft and Missionmentioning
confidence: 99%
“…Applying Ohm's law and Kirchhoff's law, an Ordinary Differential Equation (ODE) can be written for each node, thus reducing the overall transient problem to a simpler linear ODE system. In nominal conditions, the overall heat transfer rate of the heat pipe (Q) can be described using Equation (1), where ∆T is the overall temperature difference between the heat source and the heat sink, and R tot is the idealized thermal resistance network, shown in Figure 1. The total resistance of the heat pipe R tot is a combination of series and parallel resistances.…”
Section: Development Of the Numerical Toolmentioning
confidence: 99%
“…This is visible in many specific applications in the aerospace domain. For example, as far as subsonic aviation is concerned, the implementation of green and digital transitions is forcing the international community to develop new integrated thermal management solutions to deal with competing requirements, such as the presence of cryogenic fuels on board and the increased dissipated heat due to increased installed computational power [1][2][3][4][5]. Another example deals with the advancement of flight technology, where aircraft speeds transitioned from subsonic to transonic and now towards supersonic and hypersonic.…”
Section: Introduction 1thermal Management Challenges In the Aerospace...mentioning
confidence: 99%
“…With the advancement of flight technology, aircraft speeds transitioned from subsonic to transonic, and now supersonic [1][2][3][4]. Increasingly, supersonic vehicles are being used for numerous supersonic cruise missions due to consistent performance enhancements [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%